Fluororubber composite material added with modified sepiolite and preparation method of fluororubber composite material

Sepiolite is modified by acid activation method, impurities are removed and specific surface area is increased, and mechanical mixing is combined with fluoroelastomer, which solves the problem of insufficient dispersion of sepiolite in polymer matrix, and realizes the mechanical properties and heat of composite materials Improved stability.

CN119431975APending Publication Date: 2025-02-14INST OF NEW MATERIALS & IND TECH WENZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411351634.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The insufficient dispersion of natural sepiolite in polymer matrix limits its application as a nanomaterial, and the existing modification methods have limitations.

Method used

Sepiolite is modified by acid activation method, and impurities are removed by reacting with nitric acid solution, specific surface area and adsorption capacity are increased, and then mechanically kneaded with fluoroelastomer to form a closely crosslinked composite material.

Benefits of technology

It improves the dispersion and mechanical properties of sepiolite in fluoroelastic composite materials, enhances nano characteristics and thermal stability, and expands its potential for application in multiple fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431975A_ABST
    Figure CN119431975A_ABST
Patent Text Reader

Abstract

According to the fluororubber composite material added with the modified sepiolite and the preparation method of the fluororubber composite material, natural sepiolite powder is modified by adopting an acid activation method, the specific surface area and the pore size of the sepiolite subjected to acid activation are greatly improved, and mineral impurities existing in the natural sepiolite are effectively removed; compared with the original FKM composite material and the FKM composite material only added with the natural sepiolite, the tensile strength, the 100% stress at definite elongation and the hardness of the FKM composite material added with the acid activated sepiolite are respectively improved by 259%, 351% and 20.1%, in addition, the conductivity, the thermal stability and the thermal management performance of the composite material are also improved, and the color of the composite material is changed, so that the composite material can be applied to the field of electronic devices. The shading performance of the material is very good; the fluororubber composite material added with the acid-activated sepiolite powder has good mechanical and thermal properties, and has great industrial application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber processing and production, in particular to a fluororubber composite material added with modified sepiolite and a preparation method thereof. Background Art

[0002] As a natural fibrous inorganic nanofiller, sepiolite has the general chemical formula: Mg8Si 12 O 30 (OH)4(OH2)4·8H2O. The main components of sepiolite are SiO2 (accounting for more than 50%) and MgO (less than 25%), and it has been widely used in various technologies. The mineral structure of sepiolite is roughly the same as that of attapulgite. Both are hydrous aluminum magnesium silicate minerals with chain structures. The chain structures also contain small units of layered structures, which are 2:1 layer types. The difference is that the pores between the unit layers are different. The pores of the unit layers of sepiolite can be widened to The largest one can reach That is, it can accommodate more water molecules (zeolite water), making sepiolite have better physical, chemical and process properties than attapulgite. This is the key to sepiolite becoming the mineral with the best performance and wide application in this family.

[0003] However, the fibers in natural sepiolite tend to exist in the form of aggregated bundles, and sepiolite minerals are widely distributed in nature, often coexisting with attapulgite, montmorillonite, talc, etc. If natural sepiolite is directly mixed with fluororubber, its specific surface area and surface activity will be reduced. These factors limit its dispersion in the polymer matrix and its application as a nanomaterial. Currently, there are roughly three methods for modifying sepiolite: thermal modification, inorganic modification, and organic modification.

[0004] Fluororubber refers to a synthetic polymer elastomer with fluorine atoms around the carbon atoms on the main chain or side chain. Due to the introduction of fluorine atoms, CF bonds are formed in fluororubber, which has a large bond energy and can well conceal the CC main chain, thus giving fluororubber excellent heat resistance, oxidation resistance, oil resistance, chemical corrosion resistance, good physical and mechanical properties and atmospheric aging resistance. These properties make fluororubber widely used in aerospace, aviation, automobiles, petroleum and household appliances, and it is an irreplaceable key material in the cutting-edge defense industry. However, as its application becomes more and more extensive, the performance requirements for fluororubber are getting higher and higher, and the performance of a single fluororubber can no longer meet the demand. Therefore, other fillers can be used together with fluororubber to make polymer composite materials, thereby expanding the performance of fluororubber and making it applicable to more fields. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a fluororubber composite material with modified sepiolite added and a preparation method thereof. The technical solution adopted by the present invention is as follows:

[0006] In a first aspect, a method for preparing a fluororubber composite material containing modified sepiolite is provided, comprising the following steps:

[0007] S1. The acid solution is mixed with sepiolite powder, and then filtered, washed, and dried to obtain acid-activated sepiolite powder, referred to as GSEP;

[0008] S2. After mixing fluororubber and acid-activated sepiolite powder, an accelerator and a vulcanizing agent are added, and the mixture is cured on a flat vulcanizer to obtain a FKM / GSEP composite material.

[0009] Furthermore, in step S1, the sepiolite powder is first mixed with deionized water, stirred vigorously in a stirrer for 4-8 hours, and then allowed to stand for 16-20 hours, the supernatant is poured out, the remaining part is dried in an oven, and the dried sepiolite powder is mixed with an acid solution; a nitric acid solution is mixed with the sepiolite powder, the sepiolite powder is soaked in the nitric acid solution for 20-28 hours, and then filtered, and the sepiolite powder is washed with deionized water to neutrality while filtering, and after the filtration is completed, the sample is dried in an oven, and the dried sample is ground to obtain acid-activated sepiolite powder; wherein the solid-liquid ratio of the sepiolite powder to deionized water is 1:20, the stirrer is 1000r / min, and the oven temperature is 80°C for 24 hours.

[0010] Furthermore, in step S2, the fluororubber and GSEP are first mixed in a two-roll open rolling mill at a temperature of 45° C. and a roller speed of 27 r / min. After the FKM and GSEP are fully mixed, the accelerator TAIC and the vulcanizing agent are added in sequence. After mixing for 1 hour, a homogenized rubber material is obtained, and then the rubber material is cured for 10 minutes at 170° C. and a pressure of 10 MPa on a flat vulcanizer. Then, the obtained vulcanized rubber is cured at 220° C. for 24 hours to obtain a FKM / GSEP composite material.

[0011] In the above steps, the acid-activated sepiolite powder is used as the only reinforcing filler of fluororubber.

[0012] In the second aspect, the fluororubber composite material prepared by the method for preparing the fluororubber composite material with modified sepiolite added as described above also falls within the protection scope of the present invention.

[0013] The beneficial effects of the present invention are as follows: the present invention adopts an inorganic modification method and utilizes nitric acid to perform acid activation on sepiolite, which can remove mineral impurities such as talc and clear the impurity channels in the fibrous structure, thereby increasing its specific surface area and enhancing its adsorption capacity, and at the same time dispersing some aggregated fiber bundles to obtain partial monomer fibers, thereby further enhancing the nano properties; the acid-activated sepiolite is mechanically mixed with fluororubber, the acid-activated sepiolite is tightly linked to the fluororubber matrix, and strong cross-linking occurs between the fibrous structure and the molecular chains of the fluororubber, thereby improving the mechanical properties of the fluororubber composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0015] Figure 1 SEM of sepiolite before and after acid activation, (a) before acid activation, (b) after acid activation;

[0016] Figure 2 TEM before and after acid activation of sepiolite. (a) and (b) are TEM images of SEP at 500nm and 100nm, respectively. (c) and (d) are TEM images of GSEP at 500nm and 100nm, respectively. (e) is the distribution diagram of magnesium, oxygen, and silicon elements in GSEP.

[0017] Figure 3 FT-IR, XRD and BET tests of sepiolite before and after acid activation, where (a) is the FT-IR graph of SEP and GSEP, (b) is the XRD graph of SEP and GSEP, (c) is the N2 adsorption-desorption isotherm, and (d) is the change of specific surface area of ​​sepiolite before and after acid activation;

[0018] Figure 4 Mechanical properties of FKM / SEP composites, where (a) is the tensile strength of the composite, (b) is the elongation at break, (c) is the 100% elongation stress, (d) is the hardness of the composite, (e) is the stress-strain curve and the trend of tensile strength, and (f) is the elastic modulus diagram;

[0019] Figure 5SEM of tensile fracture surfaces of different composite materials, where (a) is the fracture surface of pure FKM composite material without sepiolite, (b) is the fracture surface of the composite material after adding 5phr SEP, (c) is the fracture surface of the composite material after adding 5phr GSEP, (d) is the fracture surface of the composite material after adding 10phr GSEP, (e) is the fracture surface of the composite material after adding 15phr GSEP, and (f) is the fracture surface of the composite material after adding 20phr GSEP;

[0020] Figure 6 Comparison of the electrical conductivity of different composite materials;

[0021] Figure 7 Thermogravimetric analysis of different composite materials, where (a) is the thermogravimetric curve (TG) of the composite material, (b) is the thermogravimetric differential curve (DTG) of the composite material, and (c) is the residual carbon rate of the composite material;

[0022] Figure 8 Thermal management performance diagram of different composite materials, where (a) is the infrared image extracted during heating and cooling, (b) is the heating curve, and (c) is the cooling curve;

[0023] Fig. 9 In the figure, (a) is the color brightness and hue angle of the fluororubber composite material, (b) is the a* and b* of the fluororubber composite material, (c1) is the picture of pure FKM, (c2) is the picture of FKM / SEP-5, (c3) is the picture of FKM / GSEP-5, (c4) is the picture of FKM / GSEP-10, (c5) is the picture of FKM / GSEP-15, and (c6) is the picture of FKM / GSEP-20. DETAILED DESCRIPTION

[0024] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below in conjunction with embodiments and drawings.

[0025] Example

[0026] 1. Preparation of acid-activated sepiolite

[0027] Take a certain amount of sepiolite powder and add it to a beaker filled with deionized water (solid-liquid ratio is 1:20), stir vigorously in a stirrer (1000r / min) for 6 hours and then let it stand for 18 hours. Pour out the supernatant and dry the remaining part in an oven (80℃, 24h). Prepare a concentration of 5mol·L -1The prepared nitric acid solution is mixed with the dried sepiolite powder (solid-liquid ratio is 1:3), and then filtered after soaking for 24 hours. While filtering, it is washed with deionized water until it is neutral. After filtering, the sample is dried in an oven (80℃, 24h). The dried sample is ground to obtain acid-activated sepiolite powder, which is marked as GSEP. The sepiolite that has not been acid-activated is marked as SEP.

[0028] Preparation of 2FKM / GSEP composites

[0029] FKM and GSEP were mixed in a two-roll open mill (KHB8, Guangdong Lina Industrial Co., Ltd., China) at a temperature of 45 °C and a roller speed of 27 rpm for 30 minutes. After FKM and GSEP were fully mixed, accelerator TAIC and vulcanizing agent were added in sequence. 101-50D. After mixing for 1 hour, a homogenized rubber material was obtained. First, it was cured for 10 minutes at 170°C and 10MPa pressure on a flat vulcanizer (XH-406B, Xihua Testing Instrument Co., Ltd., Dongguan, China). Finally, the vulcanized rubber was cured at 220°C for 24 hours, and the obtained sample was recorded as FKM / GSEP-5 composite material (Example 1). In addition, FKM (Comparative Example 1), FKM / SEP-5 (Comparative Example 2), FKM / GSEP-10 (Example 2), FKM / GSEP-15 (Example 3) and FKM / GSEP-20 (Example 4) were prepared under the same process parameters, and their corresponding formulas are listed in Table 1.

[0030] Table 1 FKM nanocomposites with different raw material compositions.

[0031]

[0032] Test Case

[0033] 1 Morphological characterization of sepiolite

[0034] The morphology and microstructure of sepiolite before and after acid activation were characterized by SEM. Figure 1 As shown. Figure 1 In (a), natural sepiolite powder is covered with impurities such as quartz, talc and calcite and appears in block form. The strip-shaped fiber structure can be clearly seen in the red circle. After acid activation, the calcium carbonate impurities such as calcite are removed by nitric acid, and the fibrous structure of the sepiolite itself is gradually revealed. Figure 1 In (b), the aggregated fiber bundles and individual fibers can be clearly seen. From the bulk to the fibrous structure, the specific surface area increases, the nano properties can be better reflected, and the contact area with the fluororubber matrix is ​​also increased.

[0035] Figure 2 Shown are TEM images of the morphology and microstructure of sepiolite before and after acid activation. Figure 2 (a) and (b) show transmission electron micrographs of SEP at 500nm and 100nm sizes, respectively. At 500nm, the fibrous structure of natural sepiolite was observed, most of which existed in the form of aggregated bundles, disordered, and there were a large number of mineral impurities next to the fibrous structure. These impurities were more clearly seen at 100nm. Figure 2 (c) and (d) show the transmission electron microscopy images of GSEP at 500nm and 100nm respectively. Figure 2 (c) The aggregation of the fibrous structure is significantly reduced, and some monomer fibers also appear. At a size of 100nm, a completely ordered fibrous structure can be seen with very few impurities. At the same time, EDS analysis of GSEP is performed, and the corresponding element mapping is shown in Figure 2. Figure 2 As shown in (e), Mg, O and Si are uniformly dispersed on the surface of the fibrous structure, indicating that acid activation can effectively remove calcium carbonate impurities such as calcite, without destroying the fibrous structure.

[0036] In addition, the present invention uses BET to observe the changes of SEP before and after acid activation. Figure 3 (c) is the N2 adsorption-desorption isotherm. From the small frame, it can be found that the pore size of natural sepiolite is mainly distributed around 3.65nm, while after acid activation, the pore size is mainly distributed around 4.15nm. This shows that most of the mineral impurities distributed in the sepiolite are decomposed after acid activation, resulting in the opening of the originally blocked pore channels and the increase of the pore size. Observing the N2 adsorption-desorption isotherm in the large frame, the maximum adsorption capacity of natural sepiolite is 17.3cm 3 / g, while the maximum adsorption capacity of the modified sepiolite is 55.1cm 3 / g, the adsorption amount increased by 218%. After acid activation treatment, the N2 adsorption and desorption isotherms of sepiolite moved upward, which means that the adsorption capacity of sepiolite for N2 was greatly enhanced, and more micropores and mesopores were produced, which also increased the pore size of sepiolite from the side surface. Figure 3 (d) shows the change of specific surface area of ​​sepiolite before and after acid activation. After acid activation, the specific surface area increased from 18.7 m 2 / g increased to 52.7m 2 / g. Increased by 181%. The increase in specific surface area can greatly increase the contact area between the sepiolite fiber and the fluororubber matrix, making the cross-linking between the two closer, thereby improving the mechanical properties of the composite material.

[0037] 2 Mechanical properties analysis

[0038] The present invention uses a universal material testing machine to measure the mechanical properties of the FKM nanocomposite before and after acid activation. The data of the tensile strength, elongation at break, 100% tensile stress, hardness, stress-strain and modulus of the composite material are as follows: Figure 4 (af) shown. Figure 4 (ad) shows the FKM composite material with added sepiolite. The tensile strength, 100% modulus and hardness of the original FKM are the lowest. After adding natural sepiolite, these properties of the original FKM are significantly improved. The tensile strength is increased from 4.15MPa to 10.25MPa, an increase of 146%; the analysis shows that the addition of sepiolite fiber structure can improve the interfacial bonding between the nanofiller and the fluororubber matrix and enhance the crosslinking density inside the fluororubber. When the FKM composite material is subjected to external force, the polymer chain formed between the filler and the rubber will share the external force, thereby improving the tensile strength of the composite material. Comparing the composite materials of natural sepiolite and acid-modified sepiolite, it is found that the latter has better mechanical properties and smaller errors than the former. As the amount of acid-modified sepiolite gradually increases, the tensile strength reaches a maximum of 14.9MPa, an increase of 261% compared with the original FKM, and the 100% modulus reaches a maximum of 7.23MPa, an increase of 345%. The analysis shows that after acid activation, impurities are removed from SEP, the pore size and specific surface area of ​​the SEP fiber structure are increased, the contact area with the fluororubber matrix is ​​enhanced, and the cross-linking density is higher, so the mechanical properties of the composite material are enhanced. However, the tensile strength does not increase continuously with the increase in the number of parts, but reaches the maximum value at 15phr, and decreases at 20phr.

[0039] The elongation at break decreased gradually with the continuous increase of sepiolite, from 417.5% to 196.8%, a decrease of 52.3%. Figure 4 (d) shows the hardness of the composite material. Its change trend is roughly the same as the trend of tensile strength. The original FKM has the lowest hardness. As the amount of sepiolite added gradually increases, its hardness also gradually increases, reaching a maximum of 68.5 (HA), which is 15% higher than the original FKM. On the one hand, this is because the added sepiolite nanofiller itself has a high hardness. On the other hand, the addition of sepiolite fiber structure can increase the crosslinking density of the composite material, which is conducive to the improvement of hardness.

[0040] from Figure 4 As can be seen from (e), the trends of stress-strain curve and tensile strength are corresponding. The slope of each stress-strain curve represents the elastic modulus of the composite material. Figure 4(f) The elastic modulus graph shows that as the amount of sepiolite added increases, the slope increases, and the elastic modulus also increases. From a macroscopic perspective, the elastic modulus is a measure of the ability of an object to resist elastic deformation. The larger the elastic modulus, the greater the rigidity of the surface composite material.

[0041] In order to further analyze the enhancement mechanism of the tensile properties of FKM composites, the fracture morphology of different FKM composites was observed using a scanning electron microscope. Figure 5 As shown, the fracture surface of the original FKM is relatively smooth, indicating that the tensile strength and modulus of the original FKM rubber are low. Figure 5 (b) shows the fracture surface of the composite material after adding natural sepiolite. Figure 5 (a) is much rougher, and there are many small particles or block-shaped impurities on the surface. Observing the enlarged image in the yellow circle, it can be found that there is a relatively large gap between the natural sepiolite fiber and the FKM matrix, and the interface bonding force is poor. Figure 5 The roughness of the SEM fracture surfaces of (c) to (f) increases with the increase of the amount of acid-modified sepiolite. In addition, it can be clearly seen on each fracture surface that sepiolite fibers are embedded in the FKM matrix, and the gap between the two is gradually narrowing. Figure 5 The enlarged image in (e) shows that the sepiolite fibers are well coated by FKM and the interfacial bonding strength is enhanced. Figure 5 The surface roughness of (f) is the highest, and there are many fillers gathered on the surface, which easily causes local defects, which in turn reduces the tensile strength of the composite material.

[0042] Figure 6 The figure shows the resistivity diagram of different composite materials. It can be seen from the figure that the original FKM has the lowest volume resistivity and the best conductivity. After adding natural sepiolite, the volume resistivity increases greatly and the conductivity decreases. After adding acid-modified sepiolite, the volume resistivity increases compared to the original FKM, but it is much lower than the composite material with natural sepiolite. It is speculated that the volume resistivity increases greatly because the impurities in the natural sepiolite block the channels of the sepiolite fiber structure, and the impurities themselves are not conductive. After acid modification, the impurities are removed, the sepiolite fibers are exposed, and the channels are enlarged. Therefore, the conductivity is improved. However, as the filler increases, the filler slowly gathers together, and the conductivity of the sepiolite itself is not high, so the conductivity decreases with the increase in the number of parts.

[0043] 3 Thermal stability performance

[0044] Figure 7TG, DTG and residual carbon rate of different FKM composites. From Table 2, we can see the initial decomposition temperature of each composite material. The initial decomposition temperature of the original FKM is 365.2℃. After adding natural sepiolite, the initial decomposition temperature is 357.5℃, which is 7.7℃ lower. After analysis, it is believed that the impurities in natural sepiolite are attached to the fiber structure of sepiolite in large quantities, resulting in a decrease in the degree of connection between it and the FKM matrix, which in turn destroys the inherent structure of the original FKM matrix, resulting in a decrease in the initial decomposition temperature. After adding acid-modified sepiolite, the initial decomposition temperature of the composite material increased and reached a maximum of 384.1℃ when the number of parts was 20. Compared with the original FKM, it increased by 18.9℃. After analysis, it is believed that in the process of temperature increase, sepiolite absorbs heat first, so that the composite material needs to absorb more heat to remove hydrogen fluoride, which leads to an increase in its initial decomposition temperature. In addition, nanofillers can inhibit the mobility of polymer molecules at high temperatures, and sepiolite nanofillers themselves are a high-temperature resistant inorganic substance that can also absorb heat energy. exist Figure 7 It can also be seen from the enlarged figure of a that when the weight loss rate of the composite material reaches about 20%, after adding acid-activated sepiolite, its decomposition temperature is higher than that of the original FKM, indicating that the thermal stability of the composite material is improved after adding acid-activated sepiolite.

[0045] Table 3 shows the thermal decomposition temperature and weight loss rate of the composite materials. The weight loss rates of the first decomposition peak of FKM, FKM / SEP-5, FKM / GSEP-5, FKM / GSEP-10, FKM / GSEP-15 and FKM / GSEP-20 are 5.42%, 5.53%, 7.36%, 9.77% and 9.39% respectively; the weight loss rates of the second absorption peaks are 42.4%, 42.1%, 41.5%, 44.4%, 44.4% and 43.4% respectively. The first absorption peak and the second absorption peak basically show an increasing trend. The temperature of the decomposition peak increases, and the thermal stability of the composite material is enhanced, indicating that the modified sepiolite plays a good cross-linking role in the rubber matrix. The decomposition temperature of the composite material increases, indicating that the modified sepiolite can improve the heat resistance of the rubber composite material.

[0046] Figure 7(b) shows the thermogravimetric differential curve (DGT) of the composite material. It can be seen that the composite material with acid-activated sepiolite has two decomposition processes: the first peak is the partial decomposition of the rubber and the dehydrogenation reaction; the second peak is the rapid decomposition of the rubber. It can be seen from the figure that after the addition of acid-activated sepiolite to synergistically reinforce the composite material, the decomposition peaks of FKM / GSEP-5, FKM / GSEP-10, FKM / GSEP-15 and FKM / GSEP-20 are all delayed. After analysis, due to the pore structure effect of sepiolite fiber, the interaction between sepiolite fiber and rubber matrix is ​​strengthened, which hinders the movement of rubber molecular chains, thereby delaying the thermal decomposition of rubber and improving the thermal stability of the polymer, resulting in the increase of the peak of the composite material with the increase of filler.

[0047] Table 2 Weight loss rate and corresponding temperature of different composite materials

[0048]

[0049] Table 3 Thermal decomposition temperature and weight loss rate of different composite materials

[0050]

[0051] 4 Thermal management performance

[0052] In order to visually demonstrate the effect of sepiolite modification on the thermal management properties of FKM, the temporal evolution of the surface temperature during heating and cooling was captured using an infrared thermography camera. Figure 8 (a) shows the infrared images extracted during the heating and cooling processes. During the heating process, an infrared image was taken every 10 seconds, and the time was extended to 100 seconds. During the cooling process, an infrared image was taken every 30 seconds, and the time was extended to 300 seconds. Darker colors represent lower temperatures, while lighter colors represent higher temperatures. It can be clearly seen that when the time reaches 60s, the light-colored area of ​​FKM / GSEP-15 is more than the others, indicating that the temperature rises faster than FKM, FKM / SEP-5, FKM / GSEP-5, FKM / GSEP-10 and FKM / GSEP-20. After 100s, the heater is turned off, and the peak temperatures of FKM, FKM / SEP-5, FKM / GSEP-5, FKM / GSEP-10, FKM / GSEP-15 and FKM / GSEP-20 samples reach 89.8℃, 92.2℃, 92.9℃, 91.8℃, 97.5℃ and 96.7℃, respectively. The temperature differences between different samples can be recorded, such as Figure 8 As shown in (b), it can be seen that the slope of the FKM / GSEP-15 curve is the largest, which also shows that the thermal conductivity of FKM / GSEP-15 is the best.

[0053] observe Figure 8 (a) During the cooling process, FKM / GSEP-15 has the fastest cooling rate. After 300s, its temperature drops to 31.3℃, which is lower than the temperature of most composite materials. The temperature during the cooling process is also recorded, such as Figure 8 As shown in (c), it can be seen that the slope of the FKM / GSEP-15 curve is the smallest, which also shows that the heat dissipation performance of FKM / GSEP-15 is the best. After analysis, it is believed that this composite material has good thermal conductivity, so it also has good thermal response, heating quickly and dissipating heat quickly.

[0054] from Figure 8 It can be clearly seen from (b) and 8(c) that the original FKM has the slowest heating and cooling speeds, indicating the lowest thermal conductivity. After analysis, it is believed that the original FKM lacks a uniform, compact, and ordered crystal structure, which is essential for efficient heat conduction within the material. After adding acid-activated sepiolite, the heating and heat dissipation speeds of the composite material increased, among which FKM / GSEP-15 had the best heating and heat dissipation performance. After analysis, it is believed that the tight cross-linked network structure formed between the sepiolite fiber structure and the fluororubber matrix plays a good role in heat conduction.

[0055] 5. Color Performance

[0056] Color lightness (L*), hue angle (h), redness-greenness (a*) and yellowness-blueness (b*) are the basic color parameters of FKM composites and are considered to be the most important parameters in industrial applications. Fig. 9 (a) is the color brightness and hue angle of fluororubber composite materials. For L*, 0 is pure black and 100 is pure white. L* can also represent the brightness of the sample. The larger the value, the brighter the brightness. It can be seen that after adding sepiolite, the L* value gradually decreases, indicating that the brightness of the composite material is gradually decreasing. Hue angle h: The value range is 0° to 360°. This value is calculated counterclockwise from red, indicating that the color is also gradually changing. Red is 0°, green is 120°, and blue is 240°. Figure 8 (b) shows the red, green and yellow-blue colors, -128 represents green and blue, +127 represents red and yellow. The test results show that the chromaticity of FKM composite materials is between -128 and +127. Figure 8 (c) Correspondingly, it can be clearly seen that the brightness value of the color is gradually decreasing, and the hue angle and chroma are also changing.

[0057] In summary, the present invention uses a relatively simple method to acid-activate natural sepiolite. Tests such as FTIR and XRD show that carbonate impurities such as calcite are greatly removed from the sepiolite after acid activation, thereby improving the purity of the sepiolite. BET test shows that the pore size and specific surface area of ​​the acid-activated sepiolite are increased, indicating that acid activation can increase the specific surface area of ​​sepiolite. The acid-activated sepiolite is blended and smelted with fluororubber. Because of the reduction of impurities, the increase of pore size and the increase of specific surface area, the crosslinking density and interfacial bonding force between the sepiolite fiber structure and the fluororubber matrix will be increased. Thereby, the mechanical properties of the composite material are enhanced. Compared with the original FKM, the mechanical properties are greatly improved after the addition of acid-activated sepiolite. Among them, FKM / GSEP-15 has the best performance improvement, and the tensile strength, 100% tensile stress and hardness are increased by 261%, 345% and 20.1% respectively compared with the original FKM. In addition, the conductivity of the composite material also shows that although the addition of sepiolite does not improve the conductivity of the composite material, the conductivity after acid modification is much better than that of natural sepiolite. The thermal stability and thermal management properties of the composite material are improved. The thermal stability shows that the initial thermal decomposition temperature of the composite material is 5% higher than that of the original FKM. The thermal management performance shows that the heating and heat dissipation performance of FKM / GSEP-15 is the best. The color performance also shows that it can be used in shading. In short, the carboxylation modification of natural sepiolite after acid activation can promote dispersion, remove impurities, and improve purity. At the same time, the pore size of sepiolite increases, the specific surface area increases, and the adsorption capacity also increases. It is an inorganic nanofiller that is worthy of development and utilization, and has great application potential in the field of fluororubber.

[0058] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A method for preparing a fluororubber composite material with modified sepiolite added, characterized in that: The following steps are involved: S1. The acid solution is mixed with sepiolite powder, and then filtered, washed, and dried to obtain acid-activated sepiolite powder, referred to as GSEP; S2. After mixing fluororubber and acid-activated sepiolite powder, an accelerator and a vulcanizing agent are added, and the mixture is cured on a flat vulcanizer to obtain a FKM / GSEP composite material.

2. The method for preparing the fluororubber composite material with added modified sepiolite according to claim 1, characterized in that: In step S1, a nitric acid solution is mixed with sepiolite powder, and the sepiolite powder is soaked in the nitric acid solution for 20-28 hours.

3. The method for preparing the fluororubber composite material with added modified sepiolite according to claim 1, characterized in that: In step S1, sepiolite powder is first mixed with deionized water, stirred in a stirrer for 4-8 hours and then allowed to stand for 16-20 hours, the supernatant is poured out, the remaining part is dried in an oven, and then the dried sepiolite powder is mixed with acid solution.

4. The method for preparing the fluororubber composite material with added modified sepiolite according to claim 3, characterized in that: The solid-liquid ratio of sepiolite powder to deionized water is 1:20, the stirrer is 1000r / min, and the oven temperature is 80℃ for 24h.

5. The method for preparing the fluororubber composite material with added modified sepiolite according to claim 1, characterized in that: In step S2, the fluororubber and GSEP are first mixed in a two-roll open rolling mill at a temperature of 45° C. and a roller speed of 27 r / min. After the FKM and GSEP are fully mixed, the accelerator TAIC and the vulcanizing agent are added in sequence. After mixing for 1 hour, a homogenized rubber material is obtained. The rubber material is then cured for 10 minutes at 170° C. and a pressure of 10 MPa on a flat vulcanizer. The obtained vulcanized rubber is then cured at 220° C. for 24 hours to obtain a FKM / GSEP composite material.

6. The method for preparing the fluororubber composite material with added modified sepiolite according to claim 1, characterized in that: The acid-activated sepiolite powder is used as the only reinforcing filler of fluororubber.

7. A fluororubber composite material prepared by the method for preparing a fluororubber composite material with added modified sepiolite as claimed in any one of claims 1 to 6.